The problem of pay-tv price wars for sports, particularly English football - Tan, Mabel Chai Lin (2014)
Industry liberalization and technology advancements have heightened competition for premium content on pay-TV. The most significant, and high profile, contests for such rights are for sports programmes, most notably the English Premier League (“EPL”, or, “BPL”). Such price wars by pay-TV operators have spiralled into loss-making bids and a consequent rise in consumer costs around the world. Regulatory interventions have centred on the anti-competitive aspects of exclusivity and re-distribution measures in Europe, particularly the UK. More recently, the spiral of loss-making bids in Singapore for EPL had also prompted the country to impose the new cross-carriage rule that mandated re-distribution of exclusive content.